2018
DOI: 10.1167/tvst.7.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Early Macular Vessel Density Loss in Acute Ischemic Optic Neuropathy Compared to Papilledema: Implications for Pathogenesis

Abstract: PurposeThis study compares macular and parafoveal vasculature in patients with optic disc swelling.MethodsTwenty eyes with acute nonarteritic anterior ischemic optic neuropathy (NAION), 39 eyes with papilledema at first presentation, and 22 eyes of normal subjects were imaged using optical coherence tomography angiography (OCT-A). Macular ganglion cell complex (GCC) and peripapillary retinal nerve fiber layer thicknesses were measured in addition to macula and parafovea superficial and deep vasculature.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
21
2
Order By: Relevance
“…Focusing on NAION eyes, we would like to clarify these findings based on prior published data,3,4 which, however, have not been mentioned by the authors. In contrast to the studies of Fard et al1 and Akbary et al,2 we previously reported that NAION eyes had a significant thinning of the ganglion cell inner plexiform layer minimum (GCIPL min) as early as 2.2 days after symptoms onset ( P = 0.017). In fact, the GCIPL min was abnormally thinned in more than 50% of eyes (56.3%) within a week of symptom onset 3…”
contrasting
confidence: 87%
See 2 more Smart Citations
“…Focusing on NAION eyes, we would like to clarify these findings based on prior published data,3,4 which, however, have not been mentioned by the authors. In contrast to the studies of Fard et al1 and Akbary et al,2 we previously reported that NAION eyes had a significant thinning of the ganglion cell inner plexiform layer minimum (GCIPL min) as early as 2.2 days after symptoms onset ( P = 0.017). In fact, the GCIPL min was abnormally thinned in more than 50% of eyes (56.3%) within a week of symptom onset 3…”
contrasting
confidence: 87%
“…We read with great interest the article by Fard et al1 comparing macular and parafoveal vasculature in 20 eyes with acute nonarteritic anterior ischemic optic neuropathy (NAION), 39 eyes with papilledema at first presentation, and 22 healthy eyes. They found that superficial and deep vasculature density values were significantly lower in NAION eyes compared to control and papilledema eyes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And the axonal swelling or RNFL edema resulting from the blocked axoplasm and leading to impedance in ow of RPC and retinal vessels might be severer in the site closer to the optic disc. While, Fard et al 26 have reported an early reduction of SVD and DVD in 6 × 6 mm scans but not of GCC at the acute stage within 2 weeks of onset. It might be that we missed the changes outside 3 × 3 mm scanning area in the early stage.…”
Section: Discussionmentioning
confidence: 92%
“…There are several limitations in our study, including its retrospective nature, the small number of subjects, and some loss to follow-up at 3-6 months. Here, we focused on ow alterations with time, yet visual eld loss of threshold was not analyzed in detail as previous studies showed a corresponding loss of structure and capillary density in the location of the visual eld loss 9,13,26 . Additionally, vasculature in prelaminar and laminar slabs was not evaluated due to the current limits of the technology, which may be more related to the ischemia mechanism of PCA.…”
Section: Discussionmentioning
confidence: 99%